1983
DOI: 10.3181/00379727-173-41673
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Adenylate Cyclase and Human Aging

Abstract: Adenylate cyclase activity was determined by enzymatic conversion of [32P]ATP to [32P]cAMP using peripheral lymphocytes freshly isolated from human subjects. The lymphocyte enzyme was stimulated by the potent fl-adrenergic catecholamine agonist isoproterenol and by the nonhydrolyzable GTP-analog Gpp[NH]p.' The two activators had a synergistic effect, and agonistdependent enzyme activity followed simple Michaelis-Menten kinetics with respect to isoproterenol in the presence but not in the absence of Gpp[NH]p. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…There are no published studies of the influence of age on ,-adrenoceptor density in human vasculature, but the one study of 1-adrenoceptor density in a tissue other than the lymphocyte in man showed no ageing change in receptor density in human brain (Kalaria et al, 1989). Studies of human lymphocytes suggest that changes in receptor affinity, coupling of the receptor to the stimulatory G, protein, or a diminished ability of Gs to activate adenylate cyclase are the responsible mechanisms for the ageassociated decline in ,-adrenergic responsiveness, and our data are consistent with these findings (Abrass & Scarpace, 1981;Feldman et al, 1984;Krall et al, 1983). Studies of vascular responses in older animals confirming diminished 3-adrenergic induced vascular relaxation have reported diminished ,3-adrenergic mediated cAMP accumulation (Ericsson & Lundholm, 1975;Schoeffler & Stochet, 1982;Volicer et al, 1983) again consistent with findings in human lymphocytes.…”
Section: Resultssupporting
confidence: 81%
“…There are no published studies of the influence of age on ,-adrenoceptor density in human vasculature, but the one study of 1-adrenoceptor density in a tissue other than the lymphocyte in man showed no ageing change in receptor density in human brain (Kalaria et al, 1989). Studies of human lymphocytes suggest that changes in receptor affinity, coupling of the receptor to the stimulatory G, protein, or a diminished ability of Gs to activate adenylate cyclase are the responsible mechanisms for the ageassociated decline in ,-adrenergic responsiveness, and our data are consistent with these findings (Abrass & Scarpace, 1981;Feldman et al, 1984;Krall et al, 1983). Studies of vascular responses in older animals confirming diminished 3-adrenergic induced vascular relaxation have reported diminished ,3-adrenergic mediated cAMP accumulation (Ericsson & Lundholm, 1975;Schoeffler & Stochet, 1982;Volicer et al, 1983) again consistent with findings in human lymphocytes.…”
Section: Resultssupporting
confidence: 81%